What Is the Long-term Survivorship of Primary and Revision Cemented Distal Femoral Replacements for Limb Salvage of Patients With Sarcoma?. Issue 3 (8th March 2023) - Geiger, Erik J.; Arnold, Michael T.; Hart, Christopher M.; Greig, Danielle; Trikha, Rishi; Sekimura, Troy; Eckardt, Jeffrey J.; Bernthal, Nicholas M.
Abstract: Background: Cemented endoprosthetic reconstruction after resection of primary bone sarcomas has been in common use for decades. Although multiple studies have reported the survivorship of primary endoprostheses, implant survivorship after revision surgery is less well established. Given that earlier advances in systemic therapy improved survival of patients with sarcoma, the usage of revision endoprostheses can be expected to increase and, as such, understanding revision implant survivorship will help to inform patient and surgeon expectations. Additionally, as new implants are developed that allow alternative reconstruction options, a normative dataset establishing accurate expectations for revision cemented endoprostheses is a critical benchmark by which to measure progress. Questions/purposes: (1) What is the implant survivorship free of all-cause revision for primary and revision cemented distal femoral replacements (DFRs) used in the treatment of malignant or benign tumors? (2) What are the most common indications for revision of primary and revision DFRs in an oncology population with mean follow-up of more than 10 years? (3) How does the indication for revision of a primary DFR affect the subsequent risk for and type of revision DFR complication? (4) What patient, tumor, or implant characteristics are associated with improved survivorship free of revision in cemented DFRs used in patients treated initially for primary malignant or benign tumors? Methods: This was a retrospective, comparative study using our institution's longitudinally-maintained database of 806 cemented endoprostheses starting in 1980 and assessed through December 31, 2018. In all, 365 DFRs were inserted during this time, but 14% (51 of 365) were placed for nonprimary bone tumors and 1% (5 of 365) were cementless reconstructions, leaving 309 cemented DFRs. Seventy-one percent (218 of 309) were primary implants and 29 percent (91 of 309) were revision implants (used to revise a prior DFR in all patients). During this time period, our strong bias was to use cemented stems and, thus, nearly all of our patients had cemented stems. Six percent (13 of 218) of primary DFRs were implanted more than 2 years before the study end; however, they lacked 2 years of follow-up data and, thus, were considered lost to follow-up, leaving 205 implants in the primary DFR analysis group. Only the first revision after primary DFR revision surgery was included in the revision cohort analysis. Thirty-two percent (29 of 91) of revision DFRs were second or more revision patients and were excluded, leaving 62 implants in the revision analysis group. Most patients in both groups were men (57% [117 of 205] for primary and 71% [44 of 62] for revision) who had been diagnosed with osteosarcoma (75% [153 of 205] and 73% [45 of 62] for primary and revision, respectively). The primary cohort had mean age of 26 ± 16 years with a mean follow-up of 136 ± 122 months, and the revision cohort had mean age of 31 ± 13 years (p = 0.02) with 141 ± 101 months of follow-up. Study endpoints included all-cause implant revision and cause-specific revision for soft tissue complications, aseptic loosening, structural complications (defined as periprosthetic or implant fracture), infection, or tumor progression. Planned surgery for implant lengthening procedures was excluded. Implant survivorship free from all-cause revision was calculated using a competing risk (cumulative incidence) estimator with death as a competing risk. A log-rank test using chi-square analysis was used to evaluate the differences in implant survivorship between primary DFRs and first revisions. The cause-specific incidences of implant revision were tabulated for primary and revision DFRs. Cox regression analysis investigated the odds of subsequent all-cause revision surgery for revision cemented DFRs based on the primary implant complication. A binary logistic regression analysis using age, gender, indication for revision, tumor type, infection, perioperative chemotherapy, and radiation was performed to identify factors associated with a second DFR reoperation. Relative effect sizes are reported as ORs. Results: The revision DFR cohort had a shorter mean survival to all-cause revision than the primary cohort (mean 10 years [95% CI 7 to 12] versus 18 years [95% CI 15 to 20]; p < 0.001). The most common complications necessitating revision for revision implants were periprosthetic or implant fracture in 37% (23 of 62) and aseptic loosening in 15% (9 of 62), and the type of primary implant complication was not associated with risk of subsequent all-cause revision surgery for revision implants. Stem diameter less than 15 mm was associated with repeat all-cause revision in cemented revision DFRs after controlling for resection length, stem length, implant fabrication (custom or modular), and presence of a porous collar (OR 4 [95% CI 1 to 17]; p = 0.03). No other parameters that we explored, including patient age, gender, chemoradiation history, or primary tumor diagnosis, were associated with repeat revision surgery. Conclusion: Understanding modifiable factors that can improve revision DFR survival is critical to achieving long-term limb salvage for patients with tumors around the knee. Our data suggest that utilizing implants with the largest possible stems—or at a minimum increasing the stem size over the primary implant—is important to revision cemented DFR survivorship and is an important part of our revision practice. Improving revision implants' resistance to aseptic loosening through designs that resist torsion (a common mode of cemented fixation failure)—such as with the use of custom cross-pin fabrication—may be one method to improve survivorship. Another will be improved implant metallurgy that is resistant to fatigue fracture. Next steps may include understanding the optimal ratio of femoral diaphyseal width to implant diameter in patients where anatomic constraints preclude the insertion of cemented stems 15 mm or more in diameter. Level of Evidence: Level IV, therapeutic study.